Édito - Description des vécus et interpellation des acteurs. Nouvelles improvisations à venir - Marc Daguzon; Sylvie Moussay (Recherches en Éducation)
This issue of the journal Recherches en éducation explores the notion of professional development in a critical way. He intends to mark the step of a changing era. It is a question of updating the usefulness of this notion. To profile renewed scientific perspectives and positions, it was important to describe, in detail, the strategies of involvement in the field as well as to stimulate promising work. The interest is to thus arm young researchers to continue to innovate in the sciences of education and training, on the basis of studies that are both contextual, dated but linked to the history of the dissemination of this notion: what is professional development? The question of the productive links between research and training is thus clearly addressed in this issue. In addition to the need for definition and foundation to understand what the professional development that opens the issue means, the eight articles that make up the set describe in detail what makes the subtlety of the work situations observed because situated professionally. The authors reveal and note how each situation transforms the subject, the collectives, points more or less to performativity, which makes it possible to draw a line of continuum linking each profession to the situated activities : teaching, selling, treating, training, etc. produces, each time, its own dynamic of professional development, and also makes it possible to identify transversalities.